STUDI PENGGUNAAN ANTIBIOTIKA PADA PASIEN PASKA MELAHIRKAN DI RUMAH SAKIT BERSALIN BUNDA KOTA MAKASSAR - ., Madania (Sainstek, 2012)
Study the use of antibiotics in patients with post-birth in Bunda maternity hospitals of Makassar. An investigation on the use of antibiotics deskriktif method performed with less see from the recipe that is entered in the Installation pharmacy prescription oral antibiotic use in patients with post-birth in maternity hospitals with the aim of the Bunda of Makassar to determine the level of use of antibiotics in patients based on level of postpartum GPA (Gravida The abortion). In this study indicate the level of usage prescribed antibiotics are Amoxicilin 53.04%, Amoxicilin + clavulanic acid 23.04%, 9.57% cefadroxil, ciprloksasin 8.70%, 5.65% metronidazole. Security level of drug in patients with postpartum Bunda Maternity Hospital in Makassar, rationality has met the standard treatment, namely the use of safe antibioics on postpartum mothers (Amoxicilin of penicillin groups), based on GPA (Gravida Para Abortion) is considered the first choice preparations safe at every postpartum patient.